Trichobezoar in a 17-year-old girl - da Rosa, Balbino; Larrosa, Néstor (Cirugía del Uruguay, 1970)
We have a case of tricobezoar in a 17 year-old patient with .operatory diagnosis, erradication of tumor and excellent evolution. This is a rare disease. The national case histories are revised.